Cooling water pipe for electric automobile and preparation method of cooling water pipe
By designing and synthesizing high-efficiency flame retardant for electric vehicle cooling water pipes with a double-layer structure, the problems of complex production processes and high cost in the existing technology are solved, the lightweight and performance improvement of the product is achieved, and the cooling water pipes of electric vehicle cooling water pipes are met. Requirements for use conditions.
Patent Information
- Application Number
- CN202510038822.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The production process of existing electric vehicle cooling water pipes is complex, costly and heavy, and it is difficult to meet the more demanding lightweight and performance requirements of electric vehicles.
The electric vehicle cooling water pipe design adopts a double-layer structure. The inner layer is an EPDM rubber layer and the outer layer is a short fiber reinforced EPDM rubber layer. It is synthesized by synthesis of high-efficiency flame retardant and modified phenolic resin glue. Improve the flame retardant and mechanical properties of rubber materials.
The production process is simplified, the material cost is reduced, the product is lighter, and the flame retardant effect and mechanical properties of rubber materials are improved, meeting the operating conditions requirements of electric vehicle cooling water pipes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber materials, in particular to a cooling water pipe for an electric vehicle and a preparation method thereof. Background Art
[0002] The cooling water pipe of new energy pure electric vehicles (BEVs) is one of the key components in the vehicle thermal management system. It is responsible for transmitting coolant to maintain the battery pack, motor and other key electronic components within a suitable temperature range and ensure the stability of the power battery system.
[0003] Automobile cooling pipes must have performance requirements such as high and low temperature resistance, pressure resistance, medium resistance, durability and sealing. Traditional rubber water pipes for internal combustion engine vehicles usually adopt a three-layer structure, that is, an inner rubber layer of EPDM rubber, a middle layer of fiber reinforcement layer, and an outer rubber layer of EPDM rubber. They can meet the use requirements of BEV cooling water pipes, but their production process is complex, costly, and heavy. The operating temperature and pressure of BEV cooling water pipes are lower than those of traditional fuel vehicles, and due to the anxiety of range, more stringent requirements are placed on lightweighting. Therefore, the development of cooling water pipes that meet the operating conditions of electric vehicles has become an urgent need in the industry. Summary of the invention
[0004] The object of the present invention is to provide an electric vehicle cooling water pipe and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an electric vehicle cooling water pipe and a preparation method thereof, comprising the following steps: Step 1: S11: Weigh eugenol and triethylamine, disperse them in anhydrous ethanol, and stir them to obtain a mixed solution A; disperse 2,4,6-trichloro-1,3,5-triazine in anhydrous ethanol, and stir them to obtain a mixed solution B; heat the mixed solution B to 60-70°C and add it to the mixed solution A, and control the adding speed so that the mixed solution B is added within 30-60 minutes; reflux the reaction for 8-10 hours, filter and rotary evaporate, wash the substrate with ethanol, filter, dry, recrystallize with ethyl acetate, filter again, and dry to obtain trieugenol grafted triazine; S12: Disperse 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in toluene, raise the temperature to 85-95°C, add trieugenol grafted triazine after all 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved, continue to raise the temperature to 100-105°C, react for 8-10 hours, cool, filter, wash the substrate with tetrahydrofuran, filter, and vacuum dry to obtain a flame retardant; Step 2: S21: placing aramid staple fibers in deionized water, and ultrasonically dispersing for 30 to 60 minutes to obtain aramid staple fiber dispersion; dispersing epoxy resin in deionized water, stirring for 30 to 60 minutes, and then adding blocked isocyanate, stirring to obtain a pretreatment solution; adding the aramid staple fiber dispersion to the pretreatment solution, stirring to obtain a pretreated aramid staple fiber dispersion; filtering and drying to obtain the pretreated aramid staple fibers; S22: Dissolve resorcinol in deionized water, add formaldehyde, react for 6-8 hours with sodium hydroxide as a catalyst, add dilute hydrochloric acid to adjust the pH value of the system to 7, add methacryloyl chloride and triethylamine, react at 40-50°C for 5-6 hours, and obtain a modified phenolic resin glue with a solid content of 6-8%; S23: mixing the butylpyrrolidone latex and the modified phenolic resin glue solution in a ratio of (15-20) to 100, adding ammonia water to adjust the pH value to 8-9, stirring and ripening for 20-24 hours to obtain the RFL dipping solution; S24: placing the pretreated short fibers into the RFL dipping solution, stirring for 20-30 minutes and then standing, filtering with a floc filter cloth, and drying in an oven at 100-105° C. for 2-3 hours to obtain an aramid short fiber composite; Step 3: S31: mixing the inner layer rubber material and the outer layer rubber material twice to obtain an inner layer mixed rubber material and an outer layer mixed rubber material respectively; S32: Set the head temperature to 75±2℃, the barrel section 2 temperature to 65±2℃, the barrel section 1 temperature to 60±2℃, and the feed port temperature to 50±2℃, extrude the inner layer mixed rubber compound and the outer layer mixed rubber compound, and vulcanize at 160±5℃ and a pressure of 0.55-0.65MPa for 20-30min to obtain an electric vehicle cooling water pipe with an inner rubber layer thickness of 0.5-0.6mm and an outer rubber layer thickness of 2-2.5mm.
[0006] Furthermore, in S11, the molar ratio of eugenol, triethylamine and 2,4,6-trichloro-1,3,5-triazine is (3.05-3.1):3:1.
[0007] Furthermore, in S12, the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to trieugenol grafted triazine is 1:1.
[0008] Furthermore, in S21, in the pretreated aramid staple fiber dispersion, the weight ratio of aramid staple fiber, epoxy resin, and blocked isocyanate is (7-10): (1-2): (3-5).
[0009] Furthermore, in S22, the molar ratio of resorcinol, formaldehyde and methacryloyl chloride is 1:(1.5~2):(0.3~0.5); the molar ratio of methacryloyl chloride to triethylamine is 1:1; and the molar ratio of sodium hydroxide to m-diphenol is (8~10):100.
[0010] Furthermore, in S31, the contents of each component in the inner layer rubber are, by weight, 100 parts of EPDM rubber, 80-100 parts of carbon black, 15-30 parts of light calcium carbonate, 50-60 parts of paraffin oil, 3-5 parts of zinc oxide, 1.5-2.5 parts of stearic acid, 2-4 parts of polyethylene glycol, 4-6 parts of vulcanizing agent, and 15-20 parts of flame retardant; the contents of each component in the outer layer rubber are, by weight, 100 parts of EPDM rubber, 80-100 parts of carbon black, 15-30 parts of light calcium carbonate, 50-60 parts of paraffin oil, 3-5 parts of zinc oxide, 1.5-2.5 parts of stearic acid, 2-4 parts of polyethylene glycol, 4-6 parts of vulcanizing agent, 15-20 parts of flame retardant, and 30-40 parts of aramid staple fiber composite.
[0011] Furthermore, in S31, the specific conditions of the two mixings are as follows: the conditions for the first mixing are: the air pressure of the upper push pin is 0.5±0.1MPa, the glue feeding temperature is 55±5℃, the mixing speed is 30±5phr, the mixing is 5~8min, and the glue discharge temperature is 140±5℃; at a roller spacing of 1.2±0.2mm, thin pass 3 times, the time is 5~8min; the conditions for the second mixing are: the air pressure of the upper push pin is 0.5±0.1MPa, the glue feeding temperature is 55±5℃, the mixing speed is 20±5phr, the mixing is 3~4min, and the glue discharge temperature is 90±5℃; at a roller spacing of 1.2±0.2mm, thin pass 3 times, the time is 5~8min.
[0012] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides a method for preparing a cooling water pipe for an electric vehicle having a double-layer structure, wherein the inner layer is an EPDM rubber layer, providing good sealing, heat resistance and medium resistance, and the outer layer is a short fiber reinforced EPDM rubber layer, providing excellent mechanical properties and pressure resistance. Compared with the conventional three-layer structured ordinary rubber hose reinforced with filament fibers, the present invention omits the middle fiber reinforcement layer, simplifies the production process, improves production efficiency, reduces material costs, and reduces the overall wall thickness of the product by 30% compared with the conventional three-layer structure pipe, thereby achieving lightweight.
[0013] In order to improve the performance of rubber materials, the present invention synthesizes a high-efficiency flame retardant, which is synthesized by a two-step method using 2,4,6-trichloro-1,3,5-triazine as a nitrogen source, eugenol as a carbon source, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as a phosphorus source. The synthesized flame retardant is added to the rubber material, and can produce a synergistic effect with inorganic fillers such as calcium carbonate, jointly improve the flame retardant effect of the rubber matrix, improve the safety of the rubber material during storage, transportation and use, and avoid serious losses caused by large-scale fires. Since the flame retardant prepared by the present invention contains two unsaturated double bonds, in the vulcanization process using an organic peroxide as a vulcanizing agent, it can produce a cross-linking effect similar to that of triallyl isocyanurate, shorten the vulcanization time of the rubber, and improve the strength and performance of the rubber.
[0014] When preparing the outer layer rubber compound, the present invention also adds an aramid staple fiber composite. The present invention pre-treats the aramid staple fiber with an epoxy resin; mixes the resorcinol-formaldehyde resin and the butylpyrrolidone latex to obtain an RFL dipping solution, and then adds the pre-treated aramid staple fiber to the RFL dipping solution to obtain an aramid staple fiber composite. After being treated with the RFL dipping solution, the adhesion effect between the aramid staple fiber composite and the rubber matrix is improved. The present invention also modifies the resorcinol-formaldehyde resin and introduces a carbon-carbon double bond into the side chain of the resorcinol-formaldehyde resin; during vulcanization, the flame retardant can further promote the cross-linking between the aramid staple fiber composite and the rubber matrix, thereby improving the bonding effect between the two.
[0015] In addition, it should be noted that when preparing the flame retardant, the amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide needs to be controlled. In the present invention, the reaction product of 2,4,6-trichloro-1,3,5-triazine and eugenol, the tri-eugenol grafted triazine, contains three carbon-carbon double bonds, which can react with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. After continuous experiments, it was found that when and only when 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide reacts with a carbon-carbon double bond on the tri-eugenol grafted triazine and retains two carbon-carbon double bonds, that is, the two react in a molar ratio of 1:1, the flame retardant obtained has both cross-linking effect and flame retardant properties. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Materials and sources used in the present invention: EPDM rubber comes from ARLANXEO High Performance Elastomers (Changzhou) Co., Ltd., brand Keltan ® 8550C; aramid staple fiber comes from Yantai Taihe New Materials Co., Ltd., with a length of 3 mm and a brand name of Taparan ® short fiber; the vulcanizing agent is diisopropylbenzene peroxide, which comes from Shanghai Gaoqiao Petrochemical Co., Ltd.; the polyethylene glycol is polyethylene glycol 400, which comes from Nanjing Xinhuayuan Chemical Co., Ltd.; the light calcium carbonate comes from Shijiazhuang Yitian Mineral Products Co., Ltd., with a particle size of 800 mesh; the carbon black comes from Kasong Chemical, model N550; the epoxy resin is epoxy resin E51, which comes from Hebei Linyuan Fine Chemical Co., Ltd.; the paraffin oil is paraffin oil 300, which comes from Hebei Shengkang Chemical Co., Ltd.; the butylpyrrolidone latex comes from Zhejiang Tianchen Rubber Co., Ltd., with the brand TC-P601; the blocked isocyanate comes from Covestro Polymer Co., Ltd., with the brand IMPRAFIX2794.
[0018] Embodiment 1: A cooling water pipe for an electric vehicle and a method for preparing the same, comprising the following steps: Step 1: S11: Weigh eugenol and triethylamine, disperse them in anhydrous ethanol, and stir them to obtain a mixed solution A; disperse 2,4,6-trichloro-1,3,5-triazine in anhydrous ethanol, and stir them to obtain a mixed solution B; heat the mixed solution B to 60°C and add it to the mixed solution A, and control the adding speed so that the mixed solution B is added within 30 minutes; reflux the reaction for 8 hours, filter and rotary evaporate, wash the substrate with ethanol, filter, dry, recrystallize with ethyl acetate, filter again, and dry to obtain trieugenol grafted triazine; wherein the molar ratio of eugenol, triethylamine, and 2,4,6-trichloro-1,3,5-triazine is 3.05:3:1; S12: Disperse 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in toluene, heat to 85°C, add trieugenol grafted triazine after all 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved, continue to heat to 100°C, react for 8 hours, cool, filter, wash the substrate with tetrahydrofuran, filter, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to trieugenol grafted triazine is 1:1; Step 2: S21: placing aramid staple fibers in deionized water and ultrasonically dispersing for 30 minutes to obtain aramid staple fiber dispersion; dispersing epoxy resin in deionized water and stirring for 30 minutes, and then adding blocked isocyanate and stirring to obtain a pretreatment solution; adding the aramid staple fiber dispersion to the pretreatment solution and stirring to obtain a pretreated aramid staple fiber dispersion; filtering and drying to obtain pretreated aramid staple fibers; in the pretreated aramid staple fiber dispersion, the weight ratio of aramid staple fibers, epoxy resin and blocked isocyanate is 7:1:3; S22: Dissolve resorcinol in deionized water, add formaldehyde, react for 6 hours with sodium hydroxide as a catalyst, add dilute hydrochloric acid to adjust the pH value of the system to 7, add methacryloyl chloride and triethylamine, and react at 40°C for 5 hours to obtain a modified phenolic resin glue with a solid content of 6%; wherein the molar ratio of resorcinol, formaldehyde, and methacryloyl chloride is 1:2:0.3; the molar ratio of methacryloyl chloride to triethylamine is 1:1; and the molar ratio of sodium hydroxide to resorcinol is 8:100; S23: mixing butylpyrrolidone latex and modified phenolic resin glue in a dry weight ratio of 18:100, adding ammonia water to adjust the pH value to 8, stirring and aging for 20 hours to obtain RFL dipping solution; S24: placing the pretreated short fibers into the RFL dipping solution, stirring for 20 minutes and then standing, filtering with a flocculent filter cloth, and drying in an oven at 100° C. for 2 hours to obtain an aramid short fiber composite; Step 3: S31: 100kg EPDM rubber, 80kg carbon black, 15kg light calcium carbonate, 50kg paraffin oil, 4kg zinc oxide, 2kg stearic acid, 3kg polyethylene glycol, 4kg vulcanizer, 20kg flame retardant are mixed to obtain an inner layer rubber; 100kg EPDM rubber, 80kg carbon black, 15kg light calcium carbonate, 50kg paraffin oil, 4kg zinc oxide, 2kg stearic acid, 3kg polyethylene glycol, 4kg vulcanizer, 20kg flame retardant, 35kg aramid staple fiber composite are mixed to obtain an outer layer rubber; the inner layer rubber and the outer layer rubber are mixed. The materials were mixed twice to obtain the inner layer mixed rubber material and the outer layer mixed rubber material respectively; the conditions for the first mixing were: the air pressure of the upper ejector was 0.5MPa, the temperature of the glue feed was 55℃, the mixing speed was 30phr, the mixing was 5min, and the glue discharge temperature was 140℃; at a roller gap of 1.2mm, the thin pass was performed 3 times for 5min; the conditions for the second mixing were: the air pressure of the upper ejector was 0.6MPa, the temperature of the glue feed was 60℃, the mixing speed was 25phr, the mixing was 4min, and the glue discharge temperature was 90℃; at a roller gap of 1.2mm, the thin pass was performed 3 times for 5min; S32: Set the die temperature to 75°C, the barrel section 2 temperature to 65°C, the barrel section 1 temperature to 60°C, and the feed port temperature to 50°C, extrude the inner layer mixed rubber compound and the outer layer mixed rubber compound, and vulcanize them at 160°C and a pressure of 0.6MPa for 30min to obtain an electric vehicle cooling water pipe with an inner rubber layer thickness of 0.5mm and an outer rubber layer thickness of 2mm.
[0019] Embodiment 2: A cooling water pipe for an electric vehicle and a method for preparing the same, comprising the following steps: Step 1: S11: Weigh eugenol and triethylamine, disperse them in anhydrous ethanol, and stir them to obtain a mixed solution A; disperse 2,4,6-trichloro-1,3,5-triazine in anhydrous ethanol, and stir them to obtain a mixed solution B; heat the mixed solution B to 65°C and add it to the mixed solution A, and control the adding speed so that the mixed solution B is added within 45 minutes; reflux the reaction for 9 hours, filter and rotary evaporate, wash the substrate with ethanol, filter, dry, recrystallize with ethyl acetate, filter again, and dry to obtain trieugenol grafted triazine; wherein the molar ratio of eugenol, triethylamine, and 2,4,6-trichloro-1,3,5-triazine is 3.05:3:1; S12: Disperse 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in toluene, heat to 90°C, add trieugenol grafted triazine after all 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved, continue to heat to 105°C, react for 9 hours, cool, filter, wash the substrate with tetrahydrofuran, filter, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to trieugenol grafted triazine is 1:1; Step 2: S21: placing aramid staple fibers in deionized water, and ultrasonically dispersing for 45 minutes to obtain aramid staple fiber dispersion; dispersing epoxy resin in deionized water, stirring for 45 minutes, and then adding blocked isocyanate, stirring to obtain a pretreatment solution; adding the aramid staple fiber dispersion to the pretreatment solution, stirring to obtain a pretreated aramid staple fiber dispersion; filtering and drying to obtain pretreated aramid staple fibers; in the pretreated aramid staple fiber dispersion, the weight ratio of aramid staple fibers, epoxy resin, and blocked isocyanate is 7:1:3; S22: Dissolve resorcinol in deionized water, add formaldehyde, react with sodium hydroxide as a catalyst for 7 hours, add dilute hydrochloric acid to adjust the pH value of the system to 7, add methacryloyl chloride and triethylamine, react at 45°C for 5.5 hours, and obtain a modified phenolic resin glue with a solid content of 6%; wherein the molar ratio of resorcinol, formaldehyde, and methacryloyl chloride is 1:2:0.3; the molar ratio of methacryloyl chloride to triethylamine is 1:1; and the molar ratio of sodium hydroxide to resorcinol is 8:100; S23: mixing butylpyrrolidone latex and modified phenolic resin glue in a dry weight ratio of 18:100, adding ammonia water to adjust the pH value to 8.5, stirring and aging for 22 hours to obtain RFL dipping solution; S24: placing the pretreated short fibers into the RFL dipping solution, stirring for 25 minutes and then standing, filtering with a floc filter cloth, and drying in an oven at 105° C. for 2.5 hours to obtain an aramid short fiber composite; Step 3: S31: 100kg EPDM rubber, 80kg carbon black, 15kg light calcium carbonate, 50kg paraffin oil, 4kg zinc oxide, 2kg stearic acid, 3kg polyethylene glycol, 4kg vulcanizer, 20kg flame retardant are mixed to obtain an inner layer rubber; 100kg EPDM rubber, 80kg carbon black, 15kg light calcium carbonate, 50kg paraffin oil, 4kg zinc oxide, 2kg stearic acid, 3kg polyethylene glycol, 4kg vulcanizer, 20kg flame retardant, 35kg aramid staple fiber composite are mixed to obtain an outer layer rubber; the inner layer rubber and the outer layer rubber are mixed. The materials were mixed twice to obtain the inner layer mixed rubber material and the outer layer mixed rubber material respectively; the conditions for the first mixing were: the air pressure of the upper ejector was 0.5MPa, the temperature of the glue feed was 55℃, the mixing speed was 30phr, the mixing was 5min, and the glue discharge temperature was 140℃; at a roller gap of 1.2mm, the thin pass was performed 3 times for 5min; the conditions for the second mixing were: the air pressure of the upper ejector was 0.6MPa, the temperature of the glue feed was 60℃, the mixing speed was 25phr, the mixing was 4min, and the glue discharge temperature was 90℃; at a roller gap of 1.2mm, the thin pass was performed 3 times for 5min; S32: Set the die temperature to 75°C, the barrel section 2 temperature to 65°C, the barrel section 1 temperature to 60°C, and the feed port temperature to 50°C, extrude the inner layer mixed rubber compound and the outer layer mixed rubber compound, and vulcanize them at 160°C and a pressure of 0.6MPa for 30min to obtain an electric vehicle cooling water pipe with an inner rubber layer thickness of 0.5mm and an outer rubber layer thickness of 2mm.
[0020] Embodiment 3: A cooling water pipe for an electric vehicle and a method for preparing the same, comprising the following steps: Step 1: S11: Weigh eugenol and triethylamine, disperse them in anhydrous ethanol, and stir them to obtain a mixed solution A; disperse 2,4,6-trichloro-1,3,5-triazine in anhydrous ethanol, and stir them to obtain a mixed solution B; heat the mixed solution B to 70°C and add it to the mixed solution A, and control the adding speed so that the mixed solution B is added within 60 minutes; reflux for 10 hours, filter and rotary evaporate, wash the substrate with ethanol, filter, dry, recrystallize with ethyl acetate, filter again, and dry to obtain trieugenol grafted triazine; wherein the molar ratio of eugenol, triethylamine, and 2,4,6-trichloro-1,3,5-triazine is 3.05:3:1; S12: Disperse 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in toluene, heat to 95°C, add trieugenol grafted triazine after all 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved, continue to heat to 105°C, react for 10 hours, cool, filter, wash the substrate with tetrahydrofuran, filter, and vacuum dry to obtain a flame retardant; wherein the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to trieugenol grafted triazine is 1:1; Step 2: S21: placing aramid staple fibers in deionized water and ultrasonically dispersing for 60 minutes to obtain an aramid staple fiber dispersion; dispersing epoxy resin in deionized water and stirring for 60 minutes, and then adding blocked isocyanate and stirring to obtain a pretreatment solution; adding the aramid staple fiber dispersion to the pretreatment solution and stirring to obtain a pretreated aramid staple fiber dispersion; filtering and drying to obtain pretreated aramid staple fibers; in the pretreated aramid staple fiber dispersion, the weight ratio of aramid staple fibers, epoxy resin and blocked isocyanate is 7:1:3; S22: Dissolve resorcinol in deionized water, add formaldehyde, react with sodium hydroxide as a catalyst for 8 hours, add dilute hydrochloric acid to adjust the pH value of the system to 7, add methacryloyl chloride and triethylamine, react at 50°C for 6 hours, and obtain a modified phenolic resin glue with a solid content of 6%; wherein the molar ratio of resorcinol, formaldehyde, and methacryloyl chloride is 1:2:0.3; the molar ratio of methacryloyl chloride to triethylamine is 1:1; and the molar ratio of sodium hydroxide to resorcinol is 8:100; S23: mixing butylpyrrolidone latex and modified phenolic resin glue in a dry weight ratio of 18:100, adding ammonia water to adjust the pH value to 9, stirring and aging for 24 hours to obtain RFL dipping solution; S24: placing the pretreated short fibers into the RFL dipping solution, stirring for 30 minutes and then standing, filtering with a floc filter cloth, and drying in an oven at 105° C. for 3 hours to obtain an aramid short fiber composite; Step 3: S31: 100kg EPDM rubber, 80kg carbon black, 15kg light calcium carbonate, 50kg paraffin oil, 4kg zinc oxide, 2kg stearic acid, 3kg polyethylene glycol, 4kg vulcanizer, 20kg flame retardant are mixed to obtain an inner layer rubber; 100kg EPDM rubber, 80kg carbon black, 15kg light calcium carbonate, 50kg paraffin oil, 4kg zinc oxide, 2kg stearic acid, 3kg polyethylene glycol, 4kg vulcanizer, 20kg flame retardant, 35kg aramid staple fiber composite are mixed to obtain an outer layer rubber; the inner layer rubber and the outer layer rubber are mixed. The materials were mixed twice to obtain the inner layer mixed rubber material and the outer layer mixed rubber material respectively; the conditions for the first mixing were: the air pressure of the upper ejector was 0.5MPa, the temperature of the glue feed was 55℃, the mixing speed was 30phr, the mixing was 5min, and the glue discharge temperature was 140℃; at a roller gap of 1.2mm, the thin pass was performed 3 times for 5min; the conditions for the second mixing were: the air pressure of the upper ejector was 0.6MPa, the temperature of the glue feed was 60℃, the mixing speed was 25phr, the mixing was 4min, and the glue discharge temperature was 90℃; at a roller gap of 1.2mm, the thin pass was performed 3 times for 5min; S32: Set the die temperature to 75°C, the barrel section 2 temperature to 65°C, the barrel section 1 temperature to 60°C, and the feed port temperature to 50°C, extrude the inner layer mixed rubber compound and the outer layer mixed rubber compound, and vulcanize them at 160°C and a pressure of 0.6MPa for 30min to obtain an electric vehicle cooling water pipe with an inner rubber layer thickness of 0.5mm and an outer rubber layer thickness of 2mm.
[0021] Comparative Example 1: No aramid staple fiber composite was added, and other parameters were the same as those in Example 1.
[0022] Comparative Example 2: No flame retardant was added, and other parameters were the same as those in Example 2.
[0023] Comparative Example 3: In step S12, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and trieugenol-grafted triazine are reacted at a molar ratio of 2:1, and the other parameters are the same as those in Example 3.
[0024] Experiment: According to the methods in Examples 1 to 3 and Comparative Examples 1 to 3, electric vehicle cooling water pipes with an inner diameter of 8 mm were prepared for testing, and the experimental results are shown in the following table. The test method is: Flame retardant performance test: Use UL94 horizontal vertical burning tester to test the vertical burning grade.
[0025] Mechanical properties test: Refer to GB / T 528-2019 to test the tensile strength and elongation at break of rubber materials.
[0026] Outer diameter change rate and bursting pressure test: refer to standard GB / T5563-2013 to test the product's pressure expansion and pressure bursting performance.
[0027] Pressure pulse test: According to the following requirements: select TL774 coolant, at the test pressure of 1 bar, medium temperature of 110℃, ambient temperature of 75℃, frequency of 1Hz, run 250,000 times, and observe whether there is any crack.
[0028]
[0029] Conclusion: The cooling pipe production method provided by this patent can realize the production of the cooling pipe and meet the operating conditions requirements of the cooling water pipe of pure electric vehicles.
[0030] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cooling water pipe for an electric vehicle, characterized in that: The following steps are involved: Step 1: by weight, 100 parts of EPDM rubber, 80-100 parts of carbon black, 10-20 parts of light calcium carbonate, 40-50 parts of paraffin oil, 3-5 parts of zinc oxide, 1.5-2.5 parts of stearic acid, 2-4 parts of polyethylene glycol, 4-6 parts of vulcanizing agent, and 15-20 parts of flame retardant are mixed to obtain an inner layer rubber; 100 parts of EPDM rubber, 80-100 parts of carbon black, 10-20 parts of light calcium carbonate, 40-50 parts of paraffin oil, 3-5 parts of zinc oxide, 1.5-2.5 parts of stearic acid, 2-4 parts of polyethylene glycol, 4-6 parts of vulcanizing agent, 15-20 parts of flame retardant, and 30-40 parts of aramid staple fiber composite are mixed to obtain an outer layer rubber; the inner layer rubber and the outer layer rubber are mixed twice to obtain an inner layer mixed rubber and an outer layer mixed rubber respectively; Step 2: Set the head temperature to 75±2℃, the barrel section 2 temperature to 65±2℃, the barrel section 1 temperature to 60±2℃, and the feed port temperature to 50±2℃, extrude the inner layer mixed rubber compound and the outer layer mixed rubber compound to obtain a double-layer composite tube embryo, and vulcanize it at 160±5℃ and a pressure of 0.55~0.65MPa for 20~30min to obtain an electric vehicle cooling water pipe with an inner rubber layer thickness of 0.5~0.6mm and an outer rubber layer thickness of 2~2.5mm.
2. The method for preparing a cooling water pipe for an electric vehicle according to claim 1, characterized in that: In step 1, the mixing conditions for the two times are as follows: the conditions for the first mixing are: the air pressure of the upper ejector is 0.5±0.1MPa, the glue inlet temperature is 55±5°C, the mixing speed is 30±5rpm, the mixing is 5~8min, and the glue discharge temperature is 140±5°C; at a roller spacing of 1.2±0.2mm, the thin pass is performed 3 times for 5~8min; the conditions for the second mixing are: the air pressure of the upper ejector is 0.5±0.1MPa, the glue inlet temperature is 55±5°C, the mixing speed is 20±5rpm, the mixing is 3~4min, and the glue discharge temperature is 90±5°C; at a roller spacing of 1.2±0.2mm, the thin pass is performed 3 times for 5~8min.
3. The method for preparing a cooling water pipe for an electric vehicle according to claim 1, characterized in that: In step 1, the preparation method of the flame retardant is: S1: Weigh eugenol and triethylamine, disperse them in anhydrous ethanol, and stir them to obtain a mixed solution A; disperse 2,4,6-trichloro-1,3,5-triazine in anhydrous ethanol, and stir them to obtain a mixed solution B; heat the mixed solution B to 60-70°C and add it to the mixed solution A, and control the adding speed so that the mixed solution B is added within 30-60 minutes; reflux for 8-10 hours, filter and rotary evaporate, wash the substrate with ethanol, filter, dry, recrystallize with ethyl acetate, filter again, and dry to obtain trieugenol grafted triazine; S2: Disperse 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in toluene, raise the temperature to 85-95°C, and after all the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is dissolved, add trieugenol grafted triazine, continue to raise the temperature to 100-105°C, react for 8-10 hours, cool and filter, wash the substrate with tetrahydrofuran, filter, and vacuum dry to obtain a flame retardant.
4. The method for preparing a cooling water pipe for an electric vehicle according to claim 3, characterized in that: In S1, the molar ratio of eugenol, triethylamine, and 2,4,6-trichloro-1,3,5-triazine is (3.05-3.1):3:
1.
5. The method for preparing a cooling water pipe for an electric vehicle according to claim 3, characterized in that: In S2, the molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to trieugenol-grafted triazine is 1:
1.
6. The method for preparing a cooling water pipe for an electric vehicle according to claim 1, characterized in that: The method for preparing the aramid staple fiber composite comprises the following steps: a. Place aramid staple fibers in deionized water and ultrasonically disperse for 30 to 60 minutes to obtain aramid staple fiber dispersion; disperse epoxy resin in deionized water and stir for 30 to 60 minutes, then add blocked isocyanate and stir to obtain a pretreatment solution; add the aramid staple fiber dispersion to the pretreatment solution and stir to obtain a pretreated aramid staple fiber dispersion; filter and dry to obtain the pretreated aramid staple fibers; b. Dissolve resorcinol in deionized water, add formaldehyde, react for 6-8 hours with sodium hydroxide as a catalyst, add dilute hydrochloric acid to adjust the pH value of the system to 7, add methacryloyl chloride and triethylamine, react for 5-6 hours at 40-50°C, and obtain a modified phenolic resin glue with a solid content of 6-8%; c. Mix the butylpyridine latex and the modified phenolic resin glue, add ammonia water to adjust the pH value to 8-9, stir and mature for 20-24 hours to obtain the RFL dipping solution; d. Place the pretreated short fibers into the RFL dipping solution, stir for 20 to 30 minutes, let stand, filter using a floc filter cloth, and dry in an oven at 100 to 105° C. for 2 to 3 hours to obtain an aramid short fiber composite.
7. The method for preparing a cooling water pipe for an electric vehicle according to claim 6, characterized in that: In a, in the pretreated aramid staple fiber dispersion, the weight ratio of aramid staple fiber, epoxy resin and blocked isocyanate is (7-10): (1-2): (3-5); the aramid staple fiber has a length of 0.1 mm-3 mm and an aspect ratio of 100-200.
8. The method for preparing a cooling water pipe for an electric vehicle according to claim 6, characterized in that: In b, the molar ratio of resorcinol, formaldehyde and methacryloyl chloride is 1:(1.5~2):(0.3~0.5); the molar ratio of methacryloyl chloride to triethylamine is 1:1; and the molar ratio of sodium hydroxide to m-diphenol is (8~10):
100.
9. The method for preparing a cooling water pipe for an electric vehicle according to claim 6, characterized in that: In c, the butylpyrrolidone latex and the modified phenolic resin glue are mixed in a dry weight ratio of (15-20):
100.
10. An electric vehicle cooling water pipe prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Phosphaphenanthrene flame-retardant compound containing s-triazine structure, and preparation and use thereof
CN101376665A
Phosphorus-containing flame retardant and preparation method thereof
CN101643650A
EPDM rubber compound and EPDM rubber hose
CN108485078A
Synthesis method of acrolein-modified p-tert-butylphenol acetaldehyde resin
CN109575208A
High-strength sole rubber and production process thereof
CN117050405A